Inner-heliospheric Signatures of Steadily Declining Solar Magnetic Fields and Their Possible Implications - Tanti, Harsha Avinash; Bisoi, Susanta Kumar; Datta, Abhirup; Fujiki, K. (The Astrophysical journal, 2025)
We examined solar photospheric magnetic fields for the solar cycles 21–25, covering the period 1975–2024. The unsigned photospheric magnetic fields at low latitudes (0°–45°), known as solar toroidal fields, showed a solar cycle variation with the total field strength being stronger during the maximum of cycle 25 than the maximum of cycle 24. However, the unsigned field strength of photospheric magnetic fields at high latitudes (45°–78°), known as solar polar fields, has shown a significant steady decline since around the mid-1990s. The unsigned field strength of solar polar fields, after an increase during 2015–2020, has declined again until 2024, continuing the declining trend for a long 30 yr. Also, we examined the solar wind microturbulence levels in the inner heliosphere (0.2–0.8 au), using interplanetary scintillation observations at 327 MHz, covering the period 1983–2022, that steadily declined since the mid-1990s and continued until 2022, synchronously with the solar polar fields. We found that the floor level in both solar toroidal fields and solar wind magnetic fields was reduced during the minimum of cycle 23 and recovered back during the minimum of cycle 24. In addition, a hemispherically asymmetric solar polar reversal was evident in the signed (axial) solar polar fields during cycles 21–25, with the reversal in cycle 25 for the northern hemisphere already completed but the same for the southern hemisphere yet to be completed. We discuss the implications of the long declining trend and other anomalies in solar cycle activity.